UV-Visible Absorption Study of Four-Substituted Norbornadiene-Quadricyclane System Through DFT Calculations - Edjlali, L.; Vessally, E. (Asian Journal of Chemistry, 2013)
UV-visible absorption studies of norbornadiene (1X)/quadricyclane (2X) system were carried out by density functional theory (DFT), method using 6-311++G** basis set of the GAUSSIAN 98 program. The DFT calculations indicate that the solar absorption bands of norbornadiene were shifted to the visible spectrum region through the electron withdrawing substituents more than through electron donating substituents.